Seasonal Variation in Resource Overlap Between Red Swamp Crayfish (Procambarus clarkii) and Native Species in Poyang Lake Wetland, China - Wu, Jiajia; Chen, Huili; Jin, Binsong; Winemiller, Kirk O.; Wu, Shenhao; Xu, Wang; Zhang, Huan; Wu, Xiaoping (Frontiers in Environmental Science, 2022)
Biological invasions are a significant component of current global environmental change that affect biodiversity as well as ecosystem processes and services. The red swamp crayfish (Procambarus clarkii) is one of the most invasive species worldwide, with a documented ability to deplete basal food resources and alter the structure of aquatic food webs. The red swamp crayfish has extensively invaded the Poyang Lake wetland, located in the middle reach of the Yangtze River basin. Here, we use an isotopic mixing model (MixSIAR) with data from stable isotope ratios (delta13C, delta15N) to estimate elative contributions of potential resources to the biomass of red swamp crayfish and ten common native species, and we use hierarchical clustering analysis to assess basal resource breadth and interspecific similarity of invasive and native species. We hypothesized that red swamp crayfish and several native species have similar trophic niches and may compete for basal resources. Results from the mixing model demonstrated seasonal variation in the basal resource of all species, including the red swamp crayfish and native snails, prawns, and fishes. Submerged macrophytes and detritus were estimated to be the most important sources during the rising-water season; during the high-water season, emergent macrophytes and detritus were most important; and during the falling-water season, detritus, POM, and floating macrophytes were most important. Resource overlap was substantial between the invasive crayfish and dominant native species, particularly the freshwater snail (Bellamya aeruginosa), indicating the potential exists for negative impact from competition under conditions of resource limitation.